Kajian Bencana Banjir pada Daerah Aliran Sungai Batang Merao Kota Sungai Penuh - Arimailiperi Arimailiperi; Waluyo Hatmoko (Jurnal Talenta Sipil, 2026)
Sungai Penuh City is geographically located in a flood-prone area, particularly during the rainy season. This study aims to identify the main factors contributing to flooding, determine the most dominant factor, and propose solutions for future flood management. The Analytical Hierarchy Process (AHP) was applied to analyze eight parameters: rainfall, slope, erosion/sedimentation, river narrowing, land use, deforestation, sand mining (galian C), and waste. The results indicate that human activities are the dominant factors, including land use (23.7%), river narrowing (19.4%), sand mining (15.4%), deforestation (15.3%), erosion/sedimentation (11.5%), and waste (6%). Natural factors have relatively smaller contributions, namely slope (4.5%) and rainfall (4.3%). The pairwise comparison consistency test produced a CR value ≤ 0.09, confirming the reliability of the analysis. Batang Merao River was found to be the most affected by floods, driven by high rainfall, topography, land use change, deforestation, direct waste disposal into the river, and upstream sand mining activities. These findings highlight the urgent need for integrated flood management involving government, communities, and stakeholders through spatial planning control, mining regulation, and increased environmental awareness.